2019
DOI: 10.1164/rccm.201902-0374up
|View full text |Cite
|
Sign up to set email alerts
|

Update in Chronic Obstructive Pulmonary Disease 2018

Abstract: Chronic obstructive pulmonary disease (COPD) remains a leading cause of morbidity and mortality worldwide. In this Update, we review the progress made in 2018 on mechanisms of disease, clinical epidemiology, and therapeutic options and highlight areas for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 113 publications
0
2
0
1
Order By: Relevance
“…COPD manifests as a series of overlapping phenotypes, including chronic bronchitis, emphysema, small airway disease, and frequent exacerbations. Despite differences in pathology, they share many common but complex pathogenetic processes, including inflammation, excessive oxidative stress, apoptosis, and autoimmunity [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD manifests as a series of overlapping phenotypes, including chronic bronchitis, emphysema, small airway disease, and frequent exacerbations. Despite differences in pathology, they share many common but complex pathogenetic processes, including inflammation, excessive oxidative stress, apoptosis, and autoimmunity [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, lymphocytes, especially CD4+ T cells involved in the pathogenesis of COPD, have become an active topic of research [ 3 , 5 , 6 , 12 ]. Studies have revealed that the imbalance between T helper (Th)17 cells and regulatory T (Treg) cells played a vital role in the development and outcome of COPD [ 5 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A DPOC está entre as principais causas de morbimortalidade no Brasil e no mundo, sobretudo, em casos mais avançando da doença (MIRANDA et al, 2016) configurando-se como problema global de saúde pública (XIN-XIA et al, 2020). Apesar dos fatores diretamente relacionados ao desenvolvimento dessa patologia, como o uso de tabaco, estudos apontam como fortes agentes causadores a poluição ambiental e o desmatamento (LABAKI et al, 2019).…”
Section: Aspectos Clínicos Do Paciente Com Dpocunclassified